Dukungan Kepemimpinan Organisasi dan Keberlanjutan Asuhan Keperawatan Berpusat Pada Pasien : Systematic Literature Review - Aka Pravita Septiana; Agus Sriyono; Alfonsius Kenjapluan; Shindi Hapsari (Universitas Pahlawan Tuanku Tambusai, 2025)
Patient-centered nursing care is a key pillar in improving healthcare quality and safety. This literature review aims to examine the role of organizational leadership support in sustaining patient-centered nursing practices based on studies published between 2020 and 2025. A systematic search was conducted using structured keywords in Scopus, PubMed, and ScienceDirect. Of 124 identified articles, 26 met the inclusion criteria and were thematically analyzed. The findings indicate that transformational and adaptive leadership play an essential role in enhancing staff motivation, retention, and quality of nursing care. Sustainability is further supported by adequate resource allocation and a collaborative organizational culture. However, barriers such as high workloads, resistance to change, and limited leadership training remain significant challenges. This review concludes that responsive leadership and capacity-building strategies are critical to maintaining patient-centered nursing practices. Further longitudinal and interventional studies are recommended to strengthen empirical evidence and inform nursing policy development. Keywords: leadership, patient-centered care, sustainability, nursing, quality of care